Early and Middle Adulthood Development in the Perspective of Islamic Education and Its Implications for Character Formation - Sari, Khovifah Puspita; Sya'adah, Fatihatus; Suryana, Ermis; Zulhijra, Zulhijra (Jurnal Pendidikan Islam, 2026)
The development of early and middle adulthood is a crucial phase in the course of human life. This stage is marked by physical, psychological, social, and spiritual changes. In the context of the modern era, individuals in this phase often face challenges such as economic pressure, career demands, and shifting values that influence their character. This study aims to describe the characteristics of early and middle adulthood development from an educational perspective, focusing on character formation. Using a qualitative approach with a library research method, data were obtained from Islamic literature relevant to education and moral development, as well as secondary sources such as developmental psychology books, academic articles, and Islamic education journals. The findings show that, from the perspective of Islamic education, early adulthood is a period when individuals learn to take responsibility, seek the meaning of life, and achieve personal stability. Meanwhile, middle adulthood is a phase of reflection, where individuals strive for spiritual and moral balance. Islamic values serve as a guiding foundation, helping individuals develop a strong and balanced character. The contribution of this study is to provide a clear description of how the developmental stages of adulthood can be understood through Islamic education, as well as how Islamic values can be used as an important foundation for shaping good character during this phase of development.